Physical and chemical soil variables affecting Pinus taeda L. fine roots distribution in northeast of Rio Grande do Sul, Brazil - Lopes, Vicente Guilherme; Schumacher, Mauro Valdir; Müller, Ivanor; Calil, Francine Neves; Witschoreck, Rudi; Liberalesso, Edenilson (Revista Ecologia e Nutrição Florestal - ENFLO, 2014)
This study had as objective to correlate length and fine roots biomass regarding soil chemical and physical attributes in a 15 year Pinus taeda L. stand. Soil and root samples were obtained in Cambará do Sul (RS) county, through three monoliths (25 cm x 25 cm x 40 cm) excavation. Chemical and physical samples, as well as, root sample processing were conducted at Forest Ecology Laboratory, Universidade Federal de Santa Maria. Measured edaphic variables were used on Principal Component Analysis as explanatory variables upon roots biomass and length behavior in different soil depths. Soil chemical variables showed higher correlation with roots lenght and biomass, standing out P>K>V>Mg>Ca as main variables. This higher soil chemical variables correlation is more evidenced in the layer until 10 cm of soil.